26.1: A Coarse Integral Holographic Display. Issue 1 (1st July 2013) - Smithwick, Quinn; Chen, Jhen‐Si; Chu, Daping
Abstract: A Coarse Integral Holographic Display uses coarse integral optics to angularly tile multiple elemental holograms and display large full parallax holograms with wide but different horizontal and vertical fields‐of‐view.